Intraspecific variation within Castor bean (Ricinus communis L.) based on chloroplast genomes - Muraguri, S.; Xu, W.; Chapman, M.; Muchugi, A.; Oluwaniyi, A.; Oyebanji, O.; Liu, A. (Elsevier, 2020)
The high usage of castor oil in industrial applications and bio-diesel production has led to an increase in castor bean (Ricinus communis L.) cultivation in many countries. Wild species present a source of genetic variation for germplasm improvement, often important because of their adaptation to a wide range of habitats and stresses. Chloroplast genomes are widely used in population genetics and evolutionary studies. Herein, we carried out plastome genome sequencing of 20 wild and cultivated castor bean accessions to examine plastome structural variations (PSVs). Further, single nucleotide polymorphisms (SNPs) and insertions and deletions (InDels), were identified and plastome sequences used to infer phylogenetic relationships. All the chloroplast genomes were quadripartite, with a length between 162,673 bp and 163,210 bp, with 112 genes (78 protein coding genes; PCGs, 30 tRNAs, and four rRNAs). The chloroplast genomes where conserved in terms of structure and content, with no significant PSVs detected except for a slight inverted repeat (IR) contraction in one accession. A total of 162 SNPs and 92 InDels were uncovered across the plastomes, with an average SNP and InDel density of 0.99 and 0.56 per kb respectively. Some of the non-synonymous mutations caused amino acid changes in functional domains. Intergenic spacers trnE-UUC-trnT-GGU and AccD-psaI were identified as potential barcoding regions. The phylogenetic analyses and neighbor-joining network supported three distinct lineages in castor bean. Genetic diversity was greater in one clade than the other, with implications for identifying adaptive germplasm in the wild. These results demonstrate the genetic variations and phylogenetic relationships between the wild and cultivated lineages and add insights into the origin of cultivation and spread of castor bean.